SUPER SWEET CORN BREEDING BY BACKCROSS: A NEW CHOICE FOR THE BRAZILIAN MARKET - Entringer, Geovana Cremonini; Vettorazzi, Julio Cesar Fiorio; Crevelari, Jocarla Ambrozim; DurÃ£es, Nayara Norrene Lacerda; Catarina, Renato Santa; Pereira, Messias Gonzaga (REVISTA DE AGRICULTURA, 2017)
The sweet corn market has been expanding in recent years and the trend is to maintain this growth, targeting mainly the export market. The goal was to evaluate the agronomic performance per se and hybrid backcrosses of four sweet corn populations and to estimate genetic parameters inherent in these populations, in order to achieve promising lines to obtain hybrids. The following genotypes were used for a test: the donor population sh gene,Â two recurring populations interpopulation hybrids of common maize, four sweet corn populations, and four sweet corn interpopulation hybrids. The traits evaluated were: plant height, stand, number of ears, prolificacy, number of grain rows, as well as average ear diameter, average diameter cobs, average husked ear length, average unhusked ear length, average unhusked ear weight, average husked ear weight, ear relationship, unhusked ear yieldÂ andÂ husked ear yield. Â The backcross method was efficient for obtaining sweet corn populations with good agronomic performance. Because the sweet corn interpopulation hybrid presents agronomic performance similar toP8 x C8 interpopulation hybrid, it can be inferred that all sweet corn populations backcrossed are recommended for use in obtaining lines, in order to obtain productive hybrids, or even directly as hybrid trade after further assessments.